Islamic Perspective On Land Law In Indonesia - Aisyah Aisyah (PT. Anagata Sembagi Education, 2024)
This writing has an Islamic view of land ownership in Indonesia, the discussion of which is not only the view of positive Indonesian law, but the view of Islamic Law. The aim is that it can be used as a legal comparison to broaden insight into the concept of land ownership. By comparing legal systems, we can find similarities or differences, so we can find out which one is better. The final conclusion of the writing is that there are several things, namely, First, that the concept of land ownership in positive law in Indonesia, including the Republic of Indonesia, in various applications/rules seeks to regulate the utilization, allocation and use of land for the benefit of humanity in Indonesia, and hereinafter known Ownership rules have a religious communalistic element, referring to the rule of collective rights of members of the customary law community over land, which in the customary law literature is called Ulayat Rights. The rules/concept of land ownership in customary law are: there are Ulayat rights, then the subject is the customary law community, then the object includes all land belonging to the customary law community. The rules/concept of land ownership from the perspective of Islamic law is that everything belongs to Allah Almighty, which is empowered to servants/humans, as humans we must use Allah's law, implement individual and public property rights in a balanced manner, finally there is no system of ownership/landlords. Especially for land rights related to community development, the principle of Community Based Resources Management, namely the principle of structuring natural resources of land and plantations based on the local community, should be expected. In this way, the Land Law will provide guarantees for the development of the ummah, which in turn creates a State that is bandatum toyyibatum wa Rabbun Ghafur, and spreads Rahmad for nature and all the ummah around it.